1986
DOI: 10.1366/0003702864507909
|View full text |Cite
|
Sign up to set email alerts
|

Application of Attenuated Total Reflection Infrared Spectroscopy to the Characterization of Coal

Abstract: Attenuated total reflection (ATR) spectroscopy in the infrared has been applied to the study of the surface structure of various rank coals. No special time-consuming pretreatment of the sample is required which could effect the results. The sample is simply contacted with a reflection element. The method offers a possibility of a spectral study of the surface of the coal samples with graining up to several dozens of micrometers, and the scattering effect is not observed. In the low-temperature (130°C) coal ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The observed effects of the four types of IRE on the ATR spectra of silver nanoparticles were thought to be due to the high refractive index of the sample, which consisted mainly of metallic silver; that is, the distortion of the observed ATR spectra, using the ZnSe, diamond, and Si IREs, suggested that either no ATR effect was observed, owing to inadequate internal reflection, or the ATR spectrum was distorted due to anomalous dispersion of the refractive index near the critical angle. Similar instances of this phenomenon involving band distortion of the ATR spectra have been reported, 31,32 e.g., in Tay and Kazarian’s study of petroleum heat exchanger deposits using diamond ATR. 33 However, Ge IRE proved suitable for the analysis of silver nanoparticles modified with stearic acid, even when the sample had a high refractive index, because the use of this IRE satisfies the internal reflection condition and results in no anomalous dispersion of the refractive index near the critical angle.…”
Section: Resultssupporting
confidence: 78%
“…The observed effects of the four types of IRE on the ATR spectra of silver nanoparticles were thought to be due to the high refractive index of the sample, which consisted mainly of metallic silver; that is, the distortion of the observed ATR spectra, using the ZnSe, diamond, and Si IREs, suggested that either no ATR effect was observed, owing to inadequate internal reflection, or the ATR spectrum was distorted due to anomalous dispersion of the refractive index near the critical angle. Similar instances of this phenomenon involving band distortion of the ATR spectra have been reported, 31,32 e.g., in Tay and Kazarian’s study of petroleum heat exchanger deposits using diamond ATR. 33 However, Ge IRE proved suitable for the analysis of silver nanoparticles modified with stearic acid, even when the sample had a high refractive index, because the use of this IRE satisfies the internal reflection condition and results in no anomalous dispersion of the refractive index near the critical angle.…”
Section: Resultssupporting
confidence: 78%
“…It is assumed that all carbon atoms are either aliphatic or aromatic, and the apparent aromaticity ( f a ) of the samples was estimated according to the method of Mielczarski et al: f normala = ( 100 V daf ) × 0.9677 / C The aliphatic (H al ) and aromatic hydrogen contents (H ar ) were resolved from the integrated absorbance areas ( A ) of the bands at 3100–2800 cm –1 and 900–700 cm –1 , respectively. Then, H al /H can be calculated by the following: normalH al / H = false( 1 f normala false) / ( C al / H al ) ( H / C ) The values of V daf , C, and H/C are listed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…FTIR has gained wider application since both organic functional groups [278][279][280] and mineral composition can be analyzed (e.g., clay, sulfate, slag, pottery, and oil shale) [281][282][283]. The advantages of FTIR over XRD in identifying minerals include (1) identifying both crystalline and amorphous phases, (2) distinguishing the origin of water molecules (e.g., structural water, coordinated water, and zeolitic water), and (3) performing rapid and less costly analysis [255].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%